Association of night eating habits with metabolic syndrome and its components: a longitudinal study - Junko Yoshida; Eri Eguchi; Kenjiro Nagaoka; Tatsuo Ito; Keiki Ogino (BMC, 2018)
Abstract Background Night time eating is a risk factor for metabolic syndrome and obesity. The aim of this study was to investigate whether dinner immediately before bed, snacks after dinner, or combinations of both were associated with metabolic syndrome and its components in a large Japanese cohort. Methods We enrolled 8153 adults aged 40-54 years who participated in specific medical checkups in an Okayama facility from 2009 to 2010 and from 2013 to 2014. Age-adjusted and multivariable-adjusted odds ratios of metabolic syndrome and its components in participants with both night eating habits for an average of 3.9 years were evaluated. The relative excess risk due to interaction (RERI) was utilized to determine the supra-additive interaction of both eating habits on metabolic syndrome and its components. Results The multivariable-adjusted odds ratio for obesity for those with both eating habits compared to those with neither habit was 2.11 (95% confidence interval [CI], 1.42-3.15) for men and 3.02 (95%CI, 1.72-5.29) for women. Both habits had a supra-additive interaction effect on obesity development in women (RERI, 1.67; RERI%, 85.0; p = 0.058), although this result was not significant. In women, there was an association between eating habits at night and metabolic syndrome, but in men it was unrelated. Both night eating habits were associated with dyslipidemia in men and women. Conclusions These findings suggest the need for intervention and awareness among individuals with night eating habits to mitigate further complications.